2022
DOI: 10.3389/fpsyg.2021.808434
|View full text |Cite
|
Sign up to set email alerts
|

Affective Cognition of Students’ Autonomous Learning in College English Teaching Based on Deep Learning

Abstract: Emotions can influence and regulate learners’ attention, memory, thinking, and other cognitive activities. The similarities and differences between English and non-English majors in terms of English classroom learning engagement were compared, and the significant factors affecting the emotional, cognitive, and behavioral engagement of the two groups of students in the English classroom were different. English majors’ affective engagement in the classroom was not significant, which was largely related to their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…(2019) Open-domain dialog systems To employ a multi-turn chatbot with the goal of learning and creating emotional reactions that humans are now capable of 4 participants The chatbot monitors the discussion environment and provides replies that are more emotionally suitable while doing similarly well on grammar Xie et al. (2021) Virtual reality (VR) technology To mix immersion-based English instruction with VR technology in order to increase learning results 106 Chinese Students The findings indicated that students enjoyed exploring English culture and appreciating its history and customs Zhang (2021) CNN interactive agent The research offers a convolutional neural network-based method for recognizing how learners' attention, memory, reasoning N/A This research facilitates the realization of harmonious emotional contact in the innovative learning environment in real-time and without disrupting the learners' usual online learning …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(2019) Open-domain dialog systems To employ a multi-turn chatbot with the goal of learning and creating emotional reactions that humans are now capable of 4 participants The chatbot monitors the discussion environment and provides replies that are more emotionally suitable while doing similarly well on grammar Xie et al. (2021) Virtual reality (VR) technology To mix immersion-based English instruction with VR technology in order to increase learning results 106 Chinese Students The findings indicated that students enjoyed exploring English culture and appreciating its history and customs Zhang (2021) CNN interactive agent The research offers a convolutional neural network-based method for recognizing how learners' attention, memory, reasoning N/A This research facilitates the realization of harmonious emotional contact in the innovative learning environment in real-time and without disrupting the learners' usual online learning …”
Section: Resultsmentioning
confidence: 99%
“…The authors underline the significance of emotional identification of the chatbot by offering an appropriate response to improve learners' willingness to interact and learn. Yet, out of seventeen studies, only one article ( Zhang, 2021 ) presented an empathetic detecting algorithm. In Zhang's study, the author proposed a convolutional neural network, which comprises of three convolutional layers, three pooling layers, and one connected layer to detect L2 learners' emotions and generate appropriate responses to enhance learning.…”
Section: Resultsmentioning
confidence: 99%
“…Learning input in foreign language learning is a multidimensional construct, specifically referring to the degree of effort or investment students make in language knowledge and skills and related knowledge in the learning process ( Guo and Liu, 2016 ; Yang et al, 2020 ). The most important variables positively and directly affecting foreign language learning effectiveness include behavioral, cognitive, emotional, and social input ( Liu and Guo, 2021 ; Zhang, 2022 ). However, at present, overall learner participation ( Yang et al, 2020 ) and course completion rates ( Rao and Wan, 2020 ) are low for online learning, which will inevitably impact the effectiveness of online teaching and learning.…”
Section: Literature Reviewmentioning
confidence: 99%
“… 39 However, the measurement of different intensity of FLLA between English and non-English majors has been neglected. Previous studies have given great attention to the differences between English and non-English majors in motivation, 40 , 41 engagement, 42 and learning environment. 43 These differences may reveal different learning styles of EFL learners; thereby we believed that there may be some differences in FLLA between English and non-English major students.…”
Section: Literature Reviewmentioning
confidence: 99%